Combatting neo-Colonialism in Health Research: What can Aboriginal Health Research Ethics and Global Health Research Ethics Teach Each Other?. (October 2022) - Harper, Adrian; Pratt, Bridget
The ethics of research involving Aboriginal populations and low and middle-income country populations each developed out of a long history of exploitative research projects and partnerships. Commonalities and differences between the two fields have not yet been examined. This study undertook two independent literature searches for Aboriginal health research ethics and global health research ethics. Content analysis identified shared and differently emphasised ethical principles and concepts between the two fields. Shared ethical concepts like "benefit" and "capacity development" have been developed to guide collaborations in both Aboriginal health research and global health research. However, Aboriginal health research ethics gives much greater prominence to ethical principles that assist in decolonising research practice such as "self-determination", "community-control", and "community ownership". The paper argues that global health research ethics would benefit from giving greater emphasis to these principles to guide research practice, while justice as approached in global health research ethics may inform Aboriginal health research practice. With increasing attention being drawn to the need to decolonise global health research, the lessons Aboriginal health research ethics can offer may be especially timely.